Method for improving surface hardness and wear resistance of nickel-aluminum bronze alloy by using pulse laser and product
By using pulsed laser for surface reconstitution of nickel-aluminum bronze alloy, the problem of excessive heat-affected zone and insufficient wear resistance improvement caused by continuous laser is solved, and the hardness and wear resistance of nickel-aluminum bronze alloy are significantly improved.
Patent Information
- Application Number
- CN202510002528.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, the surface modified lasers of nickel-aluminum bronze alloys are mostly high-power continuous lasers, resulting in a large thermal impact zone and affecting material performance; at the same time, the wear resistance of nickel-aluminum bronze alloys is relatively weak.
The surface reconstitution is carried out using pulsed laser to significantly improve the hardness and wear resistance of the surface of nickel-aluminum bronze alloy through rapid melting and reconstitution.
Through pulsed laser surface reconstitution treatment, the size of the heat-affected zone is reduced, and the hardness and wear resistance of the surface of nickel-aluminum bronze alloy are significantly improved, meeting the use requirements in complex working environments.
Smart Images

Figure CN119776750A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laser surface recondensation strengthening, and specifically relates to a method and a product for improving the surface hardness and wear resistance of a nickel-aluminum bronze alloy by using pulsed laser. Background Art
[0002] Nickel-aluminum bronze alloy is widely used in marine operation machinery because of its good resistance to seawater corrosion, corrosion fatigue, cavitation corrosion, and biological fouling. In addition to being used to manufacture ship propellers, it is also used in gears, water pumps, valves and other underwater pipe systems and related pipe fittings. The working environment is relatively complex and friction and wear are very likely to occur, causing serious wear and fatigue failure of key components.
[0003] Nickel aluminum bronze alloy is a widely used metal material. Many scholars at home and abroad have made a lot of research and exploration in improving its various performance areas, including but not limited to using laser cladding, laser enhanced impact, electron beam surface strengthening, electric spark surface treatment technology and other technical means to strengthen the alloy surface to meet the requirements of the working environment. However, most of the above-listed technical means are to improve the chemical or cavitation corrosion resistance of nickel aluminum bronze alloy, and the improvement of its wear resistance is relatively weak.
[0004] Laser surface resolidification strengthening technology is an advanced surface treatment technology that uses a high-energy laser beam to irradiate the metal surface to achieve rapid melting and resolidification of the material surface, thereby improving the performance of the material surface. This technology can form a strengthening layer with high hardness and good wear resistance on the surface of metal parts while maintaining a small heat-affected zone and low deformation.
[0005] Pulse lasers can release huge amounts of energy in a very short period of time, which makes them very suitable for laser surface recondensation treatments that require rapid, localized heating and rapid cooling due to their high peak power. Due to the high energy density and short pulse width of pulse lasers, the thermal action time is very short, so the size of the heat-affected zone can be effectively reduced, avoiding adverse changes in material properties, such as thermal deformation or adverse changes in microstructure.
[0006] In view of the needs of marine resource development, the wide application of nickel-aluminum bronze alloys in the field of marine operating machinery, and the excellence of pulsed laser surface resolidification technology in enhancing the surface hardness and wear resistance of alloys, it is urgent to develop a process method using pulsed laser to improve the surface hardness and wear resistance of nickel-aluminum bronze alloys.
[0007] The following problems still exist in the prior art:
[0008] (1) Laser surface resolidification strengthening technology In the field of nickel-aluminum bronze alloy surface modification, the lasers used are mostly high-power continuous lasers, and pulsed lasers are rarely used. However, the heat of continuous lasers is continuously transferred, and the heat accumulation of the material in the local area is significantly increased compared with pulsed lasers, resulting in a larger heat-affected zone, which may cause grain growth, thermal deformation of the material, and increase of residual stress, thereby affecting the final performance of the material.
[0009] (2) There are relatively few studies on the wear resistance of modified nickel-aluminum bronze alloys. In fact, during the service of nickel-aluminum bronze propellers, friction and wear are also a major cause of damage. Therefore, it is necessary to study the effect of pulsed laser on the evolution of phase composition, hardness, wear resistance and other properties of nickel-aluminum bronze alloys by laser surface resolidification. Summary of the invention
[0010] In order to solve the problems in the prior art, the purpose of the present invention is to provide a method and product for improving the surface hardness and wear resistance of nickel-aluminum bronze alloy by using pulsed laser. The method aims to rapidly melt and resolidify the surface of nickel-aluminum bronze alloy by pulsed laser technology, thereby significantly improving its surface hardness and wear resistance to meet the use requirements in complex working environments such as marine operating machinery.
[0011] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:
[0012] In one aspect, the present invention provides a method for improving the surface hardness and wear resistance of a nickel aluminum bronze alloy by using a pulsed laser, comprising the following steps:
[0013] Cleaning and pretreatment of nickel-aluminum bronze alloy surfaces;
[0014] The treated nickel-aluminum bronze alloy is placed on a workbench of a pulse laser processing system, the pulse laser parameters are set, and the pulse laser processing system is started to perform a recondensation treatment on the surface of the nickel-aluminum bronze alloy.
[0015] As a further optimization scheme of the present invention, the pretreatment method is:
[0016] Use sandpaper with different mesh sizes, and grind the cleaned nickel-aluminum bronze alloy surface in order from low to high mesh sizes until the roughness is consistent. Add pure water to assist in the grinding process. After grinding, use an ultrasonic cleaning instrument and an alcohol solution to clean the nickel-aluminum bronze alloy, and wipe it dry with dust-free paper.
[0017] As a further optimization scheme of the present invention, sandpapers with mesh sizes of 400, 1000 and 2000 are selected.
[0018] As a further optimization solution of the present invention, the laser power of the pulse laser processing is 40-100 W. More preferably, the laser power of the pulse laser processing is 100 W.
[0019] As a further optimization solution of the present invention, the laser scanning speed of the pulse laser processing is 2000-3000 mm / s. Further preferably, the laser scanning speed of the pulse laser processing is 2000 mm / s.
[0020] As a further optimization solution of the present invention, the laser pulse width of the pulse laser processing is 100-200ns. Further preferably, the laser pulse width of the pulse laser processing is 100ns.
[0021] On the other hand, the present invention provides a product obtained by a method of improving the surface hardness and wear resistance of nickel aluminum bronze alloy by using pulsed laser.
[0022] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0023] (1) The present invention uses pulsed laser rather than continuous laser to perform surface resolidification treatment on nickel-aluminum bronze alloy. The laser action time is shorter than that of continuous laser, thereby reducing the possibility of adverse thermal effects on the surface of nickel-aluminum bronze alloy.
[0024] (2) The three embodiments of the present invention all adopt the experimental method of controlling variables, and respectively explore the effects of laser power, laser scanning speed, and laser pulse width on laser surface resolidification treatment. The hardness and wear resistance of the nickel-aluminum bronze alloy surface are effectively improved in the three experimental examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the laser scanning path of the present invention.
[0026] Figure 2 This is a comparison chart of the hardness values of five groups of experimental samples A, B, C, D, and G of the present invention.
[0027] Figure 3 This is a comparison chart of the friction coefficients of five groups of experimental samples A, B, C, D, and G of the present invention.
[0028] Figure 4 This is a comparison chart of the hardness values of the three experimental groups B, E and G of the present invention.
[0029] Figure 5 This is a comparison chart of the hardness values of the three experimental groups B, F and G of the present invention. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments. However, it should be understood that the drawings are only used for exemplary description and cannot be understood as a limitation on this patent. In order to better illustrate this embodiment, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of the actual product. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted. The positional relationship described in the drawings is only for exemplary description and cannot be understood as a limitation on this patent.
[0031] A process method for improving the surface hardness and wear resistance of nickel-aluminum bronze alloy by using pulsed laser includes the following specific implementation methods.
[0032] The original samples were wire-cut to prepare 21 experimental specimens with a size of 15 mm × 15 mm × 2 mm. After cutting, they were cleaned with alcohol and wiped dry with dust-free paper to remove the chips remaining on the surface of the experimental specimens and other possible contaminants. After cleaning, they were stored in sealed bags.
[0033] The experimental samples were polished by using 400, 1000, and 2000 grit sandpapers in the order of low to high grit to polish the experimental samples to a consistent roughness. Pure water was added during the polishing process to assist in lubrication and remove abrasive debris. After polishing, the experimental samples were cleaned using an ultrasonic cleaning instrument with alcohol as the cleaning solution. After cleaning, the experimental samples were wiped dry with dust-free paper to remove residual abrasive debris and other possible contaminants on the surface of the experimental samples.
[0034] The 21 experimental specimens were divided into seven groups: A, B, C, D, E, F, and G, and numbered A1, A2, A3, B1, B2, B3, C1, C2, C3, D1, D2, D3, E1, E2, E3, F1, F2, F3, G1, G2, and G3 respectively.
[0035] Embodiment 1:
[0036] The four groups of experimental samples A, B, C, and D were clamped on the special experimental fixture to carry out the pulsed laser surface recondensation experiment; the experimental parameters of the group A samples were: laser power 40w, laser scanning speed 3000mm / s, laser frequency 1000khz, laser pulse width 200ns, line spacing 0.01mm, laser spot diameter 0.1mm, and the experimental parameters of the three groups B, C, and D were consistent with those of the group A samples except that the laser power was 60w, 80w, and 100w respectively. The experimental samples of the group G were not processed, and the laser scanning path was as follows Figure 1 shown.
[0037] The calculation formula of pulse laser energy density is as follows:
[0038]
[0039] Where E and Q are the pulse energy density of the laser (J / cm 2 〉 and single pulse energy (J); S and D represent the area of laser spot (cm 2 ) and diameter (cm), P is the average power of the laser (W), and f is the frequency of the laser (Hz). It can be seen that the laser power density of the laser surface recondensation experiment of the four groups of experimental samples A, B, C, and D is 0.5096 J / cm 2 , 0.7643J / cm 2 , 1.0191J / cm 2 , 1.2739J / cm 2 .
[0040] Furthermore, the four groups of experimental samples A, B, C, and D after the pulse laser surface recondensation treatment were cooled and then ultrasonically cleaned with an alcohol solution. After being wiped dry with dust-free paper, they were stored in sealed bags.
[0041] Furthermore, the five groups of experimental samples A, B, C, D, and G after the pulse laser surface recondensation treatment were clamped on the microhardness tester operating table. The microhardness tester operating table was moved to select the experimental sample surface without obvious defects for material hardness testing. Three points were randomly selected for measurement on each sample (the load during the hardness test was 100gf and the holding time was 15s), and the hardness values were recorded. After removing the maximum and minimum hardness values of the 9 hardness test points of the three experimental samples in each group, the average value was calculated as the hardness value of the experimental sample in this group. The comparison results of the hardness values of the experimental samples in each group are shown in Figure 2. Figure 2 shown.
[0042] Depend on Figure 2 It can be seen that the hardness value of the blank experimental sample in group G is 183.8202hv. The hardness values of the experimental samples in groups A and B after pulsed laser surface recondensation treatment are lower than those of the blank samples in group G. The hardness values of the experimental samples in groups C and D after pulsed laser surface recondensation treatment are higher than those of the blank samples in group G. Furthermore, it can be found that with the increase of pulsed laser power density, the hardness values of the experimental samples in groups A, B, C, and D also increase steadily. The laser power of the four experimental samples in group D is 100w and the laser power density is 1.2739J / cm 2 The surface hardness reaches the maximum: 214.7437hv. It can be seen that choosing the appropriate laser power can effectively improve the surface hardness of nickel-aluminum bronze alloy.
[0043] Furthermore, the five experimental samples of groups A, B, C, D, and G after the pulse laser surface recondensation treatment were clamped on the operating table of the friction and wear testing machine, and the direction perpendicular to the horizontal scanning direction of the laser was selected as the reciprocating direction of the "grinding ball" (the "grinding ball" used a ceramic ball with a diameter of 6.35 mm and a G5 grade). The load of the friction and wear testing machine was 15N. The specific friction time was determined according to the time when the friction coefficient curve of the metal material tended to be stable (the experiment could be stopped only when the friction coefficient curve of each group was stable for more than 200s). The average friction coefficient of each group of experimental samples 100s before the friction test was stopped was taken as the friction coefficient of the experimental samples in this group. The comparison results of the friction coefficients of the experimental samples in each group are shown as follows: Figure 3 shown.
[0044] Depend on Figure 3 It can be seen that the friction coefficient of the blank experimental sample in group G is 0.3575. The friction coefficients of the experimental samples in groups A, B, C, and D after pulsed laser surface recondensation treatment are all lower than those of the blank sample in group G. Under the premise that the other parameters are fixed, with the increase of laser power, the friction coefficients of the experimental samples after pulsed laser surface recondensation treatment continue to decrease, but the decreasing trend is gradually slowing down. The laser power of the four groups of experimental samples in group D is 100w and the laser power density is 1.2739J / cm 2 The friction coefficient is the smallest: 0.2089; further, the lower the friction coefficient measured by the friction and wear testing machine, the better the wear resistance of the material. Therefore, it can be seen that choosing the appropriate laser power can effectively improve the wear resistance of the nickel-aluminum bronze alloy surface.
[0045] A large number of studies have shown that when the nickel-aluminum bronze alloy is subjected to surface resolidification treatment using pulsed laser, the surface of the nickel-aluminum bronze alloy undergoes rapid melting and resolidification, and the surface of the cast nickel-aluminum bronze contains defects such as shrinkage cavities. After surface resolidification treatment, some casting defects can be eliminated, and the rapid melting and resolidification process can promote the transformation of the surface phase composition of the nickel-aluminum bronze, and the α phase is transformed into the β' phase and the κ phase. The hardness and wear resistance of the β' phase are better than those of the α phase. In addition, combined with the laser energy density calculation formula, it can be seen that under the premise that other process parameters remain unchanged, the laser energy density increases with the increase of laser power. Due to the increase in input energy, the area and depth of the molten pool formed on the surface of the nickel-aluminum bronze increase, the heat-affected zone is larger, and the treatment effect is better. In summary, increasing the laser power can increase the heat-affected zone, improve the degree of surface defect elimination and phase composition transformation of the nickel-aluminum bronze, and thus improve its surface hardness and wear resistance.
[0046] Embodiment 2:
[0047] It can be seen from the pulse laser energy density calculation formula in Example 1 that the pulse laser energy density is only related to three parameters: laser power, spot diameter, and laser frequency. Under the premise that the laser energy density is not changed in Example 1, the laser scanning speed is changed to perform Example 2.
[0048] The experimental samples of group E were clamped on the special experimental fixture to carry out the pulsed laser surface recondensation experiment. The experimental parameters were: laser power 60w, laser scanning speed 2000mm / s, laser frequency 1000khz, laser pulse width 200ns, line spacing 0.01mm, laser spot diameter 0.1mm, and laser scanning path as shown in Figure 1 shown.
[0049] Furthermore, the experimental samples of group E after the pulse laser surface recondensation treatment were cooled and then ultrasonically cleaned with an alcohol solution, and then wiped dry with dust-free paper and stored in a sealed bag.
[0050] Furthermore, the E group of experimental samples after the pulse laser surface recondensation treatment were clamped on the microhardness tester operating table, and the microhardness tester operating table was moved to select the experimental sample surface without obvious defects for material hardness test. Three points were randomly selected for measurement on each sample (the load was 100gf and the holding time was 15s during the hardness test), and the hardness values were recorded. After removing the maximum and minimum hardness values of the 9 hardness test points of the 3 experimental samples, the average value was calculated as the hardness value of the experimental sample in this group. The comparison results of the hardness values of the three groups of experimental samples B, E, and G are shown in Figure 2. Figure 4 shown.
[0051] Depend on Figure 4 It can be seen that the hardness value of the experimental samples in group E after pulsed laser surface recondensation treatment is 195.0341hv, which is higher than that of the experimental samples in group B and the blank samples in group G. It can be seen that the laser scanning speed is also an important parameter affecting the experimental results; combined with the laser energy calculation formula, it can be seen that under the premise of only changing the laser scanning speed, the laser energy density is constant. When the laser scanning speed is changed, only the number of laser treatments per unit area is changed, that is, the laser spot overlap rate is changed; in summary, under the premise of keeping other parameters unchanged, reducing the laser scanning speed can increase the laser spot overlap rate, improve the elimination of surface defects of nickel-aluminum bronze and the degree of phase composition transformation, and thus improve the surface hardness of nickel-aluminum bronze alloy.
[0052] Embodiment 3:
[0053] It can be seen from the pulse laser energy density calculation formula in Example 1 that the pulse laser energy density is only related to three parameters: laser power, spot diameter, and laser frequency. Under the premise that the laser energy density is not changed in Example 1, the laser pulse width is changed to perform Example 3.
[0054] The F group of experimental samples were clamped on the special experimental fixture to carry out the pulsed laser surface recondensation experiment. The experimental parameters were: laser power 60w, laser scanning speed 3000mm / s, laser frequency 1000khz, laser pulse width 100ns, line spacing 0.01mm, laser spot diameter 0.1mm, and laser scanning path as shown in Figure 1shown.
[0055] Furthermore, the experimental samples of group F after the pulse laser surface recondensation treatment were cooled and then ultrasonically cleaned with an alcohol solution, and then wiped dry with dust-free paper and stored in a sealed bag.
[0056] Furthermore, the F group of experimental samples after pulse laser surface recondensation treatment were clamped on the microhardness tester operating table, and the microhardness tester operating table was moved to select the experimental sample surface without obvious defects for material hardness test. Three points were randomly selected for measurement on each sample (the load was 100gf and the holding time was 15s during the hardness test), and the hardness values were recorded. After removing the maximum and minimum hardness values of the 9 hardness test points of the 3 experimental samples, the average value was calculated as the hardness value of the experimental sample in this group. The comparison results of the hardness values of the three groups of experimental samples B, F, and G are shown in Figure 2. Figure 5 shown.
[0057] Depend on Figure 5 It can be seen that the hardness value of the experimental samples in group F after pulsed laser surface recondensation treatment is 185.471hv, which is higher than that of the experimental samples in group B and the blank samples in group G. It can be seen that the laser pulse width is also an important parameter affecting the experimental results; combined with the laser energy calculation formula, it can be seen that under the premise of only changing the laser pulse width, the laser energy density and single pulse energy are constant. When the laser pulse width is changed, only the single laser action time is changed, thereby changing its peak power; in summary, under the premise of keeping other parameters unchanged, reducing the pulse width can increase the laser peak power, improve the elimination of surface defects and the degree of phase composition transformation of nickel-aluminum bronze, and thus improve the surface hardness of nickel-aluminum bronze alloy.
[0058] Combining the experimental results of Examples 1, 2, and 3, it can be seen that pulsed laser surface recondensation treatment can change the hardness and wear resistance of the nickel-aluminum bronze alloy surface, and selecting appropriate laser parameters can significantly improve the hardness and wear resistance of the nickel-aluminum bronze alloy surface.
[0059] The present invention is described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for improving the surface hardness and wear resistance of nickel aluminum bronze alloy by using pulsed laser, characterized in that: The steps include: Cleaning and pretreatment of nickel-aluminum bronze alloy surfaces; The treated nickel-aluminum bronze alloy is placed on a workbench of a pulse laser processing system, the pulse laser parameters are set, and the pulse laser processing system is started to perform a recondensation treatment on the surface of the nickel-aluminum bronze alloy.
2. The method for improving the surface hardness and wear resistance of nickel aluminum bronze alloy by using pulsed laser according to claim 1, characterized in that: The pretreatment method is: Use sandpaper with different mesh sizes, and grind the cleaned nickel-aluminum bronze alloy surface in order from low to high mesh sizes until the roughness is consistent. Add pure water to assist in the grinding process. After grinding, use an ultrasonic cleaning instrument and an alcohol solution to clean the nickel-aluminum bronze alloy, and wipe it dry with dust-free paper.
3. The method for improving the surface hardness and wear resistance of nickel aluminum bronze alloy by using pulsed laser according to claim 2, characterized in that: Use 400 grit, 1000 grit, and 2000 grit sandpaper.
4. The method for improving the surface hardness and wear resistance of nickel aluminum bronze alloy by using pulsed laser according to claim 1, characterized in that: The laser power of pulse laser processing is 40-100w.
5. The method for improving the surface hardness and wear resistance of nickel aluminum bronze alloy by using pulsed laser according to claim 4, characterized in that: The laser power of pulse laser processing is 100w.
6. The method for improving the surface hardness and wear resistance of nickel aluminum bronze alloy by using pulsed laser according to claim 1, characterized in that: The laser scanning speed of pulse laser processing is 2000-3000mm / s.
7. The method for improving the surface hardness and wear resistance of nickel aluminum bronze alloy by using pulsed laser according to claim 6, characterized in that: The laser scanning speed of pulse laser processing is 2000mm / s.
8. The method for improving the surface hardness and wear resistance of nickel aluminum bronze alloy by using pulsed laser according to claim 1, characterized in that: The laser pulse width of pulse laser processing is 100-200ns.
9. The method for improving the surface hardness and wear resistance of nickel aluminum bronze alloy by using pulsed laser according to claim 8, characterized in that: The laser pulse width of pulse laser processing is 100ns.
10. A product obtained by the method for improving the surface hardness and wear resistance of nickel-aluminum bronze alloy by using pulsed laser as described in any one of claims 1 to 9.